Effects of water deficit on urban forest growth in a dryland South American region. - Martinez, Claudia Fernanda (2013)
Urban forests located in dryland regions of Argentina are sustained mostly by groundwater and water coming from thawing in the Andes. This is because the most commonly planted tree species have high water requirements and are most often exposed to water shortage. This study assessed the effect of water deficit on diverse growth variables in saplings of Acacia visco (native tree species) and Morus alba (exotic tree species), two common tree species in the urban forests of Mendoza’s Metropolitan Area. Saplings were exposed to different levels of water deficit under controlled nursery conditions during three growing seasons. There were three watering treatments: replacement of (1) 100% transpired water (control treatment or T1), (2) 66% transpired water (moderate water deficit treatment or T2), and (3) 33% transpired water (severe water deficit treatment or T3). The impact of water stress was greater in the exotic tree-species, M. alba. The growth variables height, stem diameter, leaf area, and annual tree-ring width showed no significant differences between T1 and T2 in A. visco. In T3, tree growth was reduced in both species compared to T1. However, M. alba trees were more sensitive to any water deficit than A. visco. This latter species showed more resistance than M. alba to moderate water stress conditions, which even promoted growth of A. visco. These results highlight the importance of selecting tree species with low water consumption in sustainable urban forests of cities located in dryland environments.